Is Intracranial Pressure Monitoring of Patients With Diffuse Traumatic Brain Injury Valuable? An Observational Multicenter Study. Issue 3 (8th October 2015) - Yuan, Qiang; Wu, Xing; Cheng, Hongwei; Yang, Chaohua; Wang, Yuhai; Wang, Ersong; Qiu, Binghui; Fei, Zhimin; Lan, Qing; Wu, Sirong; Jiang, Yunzhao; Feng, Hua; et al.
Abstract: BACKGROUND: Although intracranial pressure (ICP) monitoring of patients with severe traumatic brain injury (TBI) is recommended by the Brain Trauma Foundation, any benefits remain controversial. OBJECTIVE: To evaluate the effects of ICP monitoring on the mortality of and functional outcomes in patients with severe diffuse TBI. METHODS: Data were collected on patients with severe diffuse TBI (Glasgow Coma Scale [GCS] score on admission <9 and Marshall Class II-IV) treated from January 2012 to December 2013 in 24 hospitals (17 level I trauma centers and 7 level II trauma centers) in 9 Chinese provinces. We evaluated the impact of ICP monitoring on 6-month mortality and favorable outcome using propensity score–matched analysis after controlling for independent predictors of these outcomes. RESULTS: ICP monitors were inserted into 287 patients (59.5%). After propensity score matching, ICP monitoring significantly decreased 6-month mortality. ICP monitoring also had a greater impact on the most severely injured patients on the basis of head computed tomography data (Marshall computed tomography classification IV) and on patients with the lowest level of consciousness (GCS scores 3-5). After propensity score matching, monitoring remained nonassociated with a 6-month favorable outcome for the overall sample. However, monitoring had a significant impact on the 6-month favorable outcomes of patients with the lowest level of consciousness (GCS scores 3-5). CONCLUSION: ICP monitor placement was associated with a significant decrease in 6-month mortality after adjustment for the baseline risk profile and the monitoring propensity of patients with diffuse severe TBI, especially those with GCS scores of 3 to 5 or of Marshall computed tomography classification IV.